2011
DOI: 10.1007/s11892-011-0242-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pumps in Pregnancy: Using Technology to Achieve Normoglycemia in Women with Diabetes

Abstract: Poorly controlled diabetes before conception and during pregnancy among women with pre-existing diabetes can cause major birth defects and spontaneous abortions, as wells as abnormal fetal growth and development including an offspring who is small or large for gestational age, or predisposed to obesity, type 2 diabetes, and metabolic syndrome in his/her lifetime. Conversely, for a woman with pre-existing diabetes, optimizing blood glucose levels before and during early pregnancy can reduce these risks dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Few drug studies have been performed in this population, and most evidence is observational. Insulin pumps are becoming a popular treatment modality, but studies have yet to prove that they are superior to multiple daily injections [38]. …”
Section: Diagnosis and Treatment Of Gdmmentioning
confidence: 99%
“…Few drug studies have been performed in this population, and most evidence is observational. Insulin pumps are becoming a popular treatment modality, but studies have yet to prove that they are superior to multiple daily injections [38]. …”
Section: Diagnosis and Treatment Of Gdmmentioning
confidence: 99%
“…CGM use throughout every trimester can provide pregnant women, their followers, and their health care The first successful use of CSII in pregnancy was reported in 1978, the same year that the Auto Syringe, the initial commercial subcutaneous insulin pump, was introduced in the United States and United Kingdom. [76][77][78][79] Since then, insulin pumps have undergone numerous iterations and improvements in design and functionality. 79 CSII delivers short-acting insulin in micro-boluses via a subcutaneously applied catheter.…”
Section: Safety and Efficacy Of Cgm In Pregnancymentioning
confidence: 99%
“…13 Despite the increased uptake and improvement in glycemic control, strong evidence for maternal and neonatal outcomes is lacking. 76,83,85,86,[89][90][91] A secondary analysis from the CONCEPTT study showed that the improved glucose control in pregnancy with use of CGM did not differ when comparing MDI vs CSII users. 87 MDI users did, however, experience more pronounced reductions in their HbA1c.…”
Section: Safety and Efficacy Of Csii In Pregnancymentioning
confidence: 99%
“…It causes many complications including cardiovascular diseases, nephropathy, stroke and retinopathy 1, 2. Moreover, diabetes with pregnancy is more complicated since hyperglycemia can lead to congenital malformations, preterm delivery, preeclampsia, macrosomia, shoulder dystocia, cesarean delivery and maternal mortality 3. Currently, the rapid development of continuous glucose monitoring (CGM) device brings new insights into the treatment of diabetic patients including those during pregnancy.…”
Section: Introductionmentioning
confidence: 99%